East/West Exclusions and Discourses on Population in the 20th century - Attila Melegh (Hungarian Demographic Research Institute, 2002)
This paper contributes to the comparative studies of population policies and discourses with the intention of finding such teleologically not biased interpretative frameworks in which both Western" and "Eastern" histories can be linked to each other without setting up Eurocentric or West centric comparative structures. In other words we look for such interpretative grounds, which do not fix "Western" arrangements as norms to be followed by other regions of the world or as ones having superior characteristics.
Keywords: 300; Ausländer; Migrationspolitik; Ungarn; EU-Staaten; Migranten